Dynamics of a light beam suffering the influence of a dispersing mechanism with tunable refraction index - Da Costa, Diogo Ricardo [UNESP]; De Carvalho, R. Egydio [UNESP] (American Physical Society (APS), 2018)
The dynamics of a monochromatic light beam is studied inside the oval billiard with an inner scatter circle, which can be interpreted as a cross section of a long optical fiber. The outer oval boundary acts as a perfect reflector for the light beam while the scatter circle encloses a medium with changeable refraction index. The light beam refracts when it enters inside this circle and some drastic changes in the phase space are observed. The increase of the refractive index destroys the center of stability in the phase space leading to a spread of scattered light and the islands of traps for the light propagation become more pulverized. Numerical results are presented and discussed.